Prevalence of Intimate Partner Violence and Associated Factors Among Married Nepalese Men in Kathmandu Metropolitan City - Devkota, Pooja; Niraula, Surya Raj; Singh, Suman Bahadur; Adhikari, Baikuntha Raj; Chakravartty, Avaniendra (Journal of Nepal Health Research Council, 2021)
Background: Intimate Partner Violence is defined as the intentional use of physical force, or power, threatened or actual against on self/others or groups that results in injury, death, psychological harm. Methods: A community-based cross-sectional study was conducted in Kathmandu Metropolitan city in 2018. An adequate sample of 210 married men was selected from randomly selected 10 wards of Kathmandu Municipality. A semi-structured questionnaire including standard scales was used for data collection. Multivariate analysis was performed to find out the association of Intimate Partner Violence with different variables.Results: The mean age of male respondents was 40.19 years. More than half of the respondents were Janajatis. Overwhelming respondents were Hindu (religion). Intimate Partner Violence was estimated in forms of Physical violence, 31.9%, Sexual violence, 4.3%, and Psychological violence, 50.5%. Age, age at marriage, marriage type, marriage decision, spousal age gap, family income, education, smoking habit and depression were independently associated with violence. However, family income and education were found to be significant factors associated with violence even after adjusting the effects of other potential factors.Conclusions: Strong association of Intimate Partner Violence with family income, and education of male respondents was observed. More than half of the males had psychological violence and nearly one-third of the participants had Physical violence. The study concludes that Intimate Partner Violence among males could not be neglected.Keywords: Intimate partner violence; married men; Nepal